Student Satisfaction in Terms of Creativity and Mastery of Lecturer Materials in Online Learning - Francisca Lisa Andriyani; Apri Damai Sagita Krissandi; Haryanto Haryanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze the level of student satisfaction with Indonesian language lecturers in terms of creativity and material mastery during online lectures for second semester students of the 2020/2021 academic year at Sanata Dharma University. The number of samples as many as 150 students were selected randomly by using probability sampling technique of simple random sampling type. Sampling in the study was calculated using the minimum sample determination table according to Krejcie and Morgan with a 95% confidence level. This type of research is survey research with a quantitative descriptive approach and uses a survey research design with descriptive analysis techniques. The instruments used to measure creativity and mastery of lecturer materials are questionnaires, observations, and interviews. The criteria used refer to the criteria for the percentage of success intervals, namely very high, high, medium, less and very less. The results showed that the level of student satisfaction with subject teachers, creativity skills and mastery of lecturer materials in online learning obtained an average score in the very high category.